REASONS FOR INCREASED CONSUMPTION OF UTILITIES FOR THE MAINTENANCE OF COMMON FACILITIES IN MULTI-UNIT APARTMENT BUILDINGS - Filimonov, Sergey (Revista Inclusiones, 2020)
The purpose of this work is to analyze the causes of increased consumption of utilities for the maintenance of common facilities in multi-unit apartment buildings. When managing a multi-unit apartment building, consumers of utilities (resources) receive and pay only for the resources they consume, depending on the degree of the house improvement. Consumers pay for electricity, cold and hot water, as well as water disposal for individual consumption and utilities for the maintenance of common facilities. Consumers of utilities in a multi-unit apartment building are not interested in reducing consumption of utilities for the maintenance of common facilities, as they pay for these resources not according to the actual volume of consumption, but according to the standards established by the state authorities of the constituent entities of the Russian Federation. The difference in payment for the actually consumed utilities for the maintenance of common facilities and, according to the established standards and the current legislation, is entrusted to the managing organizations, without the right to compensate for the losses incurred. Such legislative regulation leads to loss-making activities of managing organizations and, in some cases, to their bankruptcy. Consequently, management organizations are forced to look for reasons for increased consumption of utilities for the maintenance of common facilities to minimize them in the future.